TRABECULECTOMY VERSUS TUBE OUTCOME IN NEOVASCULAR GLAUCOMA - Syahiqoh, Daisy Syakhsiatusy; Rahmi, Fifin L.; Denti Puspasari; Maharani (Majalah Oftalmologi Indonesia, 2023)
Introduction: Neovascular glaucoma (NVG) is known to be a refractory form of glaucoma, which frequently requires the integrated use of medical, laser and incisional surgery. Tube-shunt implantation and trabeculectomy with anti-fibrotic agent are the two most-popular incisional procedures for managing refractory glaucoma. This study aims to compare surgical outcome between patients who underwent trabeculectomy versus tube-shunt implantation for the treatment of NVG. Methods: A retrospective study was held of NVG patients that underwent trabeculectomy and tube-shunt implantation between January 2020 - December 2022 at Dr. Kariadi Hospital, Semarang. IOP outcome and success rate was measured at 3 months post operatively. Statistical analysis was used to compare the outcome between groups, p<0.05 was considered significant. Result: There were no significant differences in characteristics between groups at baseline. Mean IOP measured at 3 months postoperatively was 18.58 ± 5.53 and 15.94 ± 10.79 in trabeculectomy and tube group respectively (p=0.04), complete success rate was 18.8% in trabeculectomy and 25% in tube group, qualified success rate was 37.5% in trabeculectomy and 56.3% in tube group. Greater failure rate was observed in trabeculectomy group (43.8%). Conclusion: Compared to trabeculectomy, tube-shunt implantation has lower IOP at 3 months postoperatively in NVG. Similar number of anti-glaucoma medications was needed postoperatively in both procedure. Greater qualified success rate was achieved in tube-shunt implantation. Greater failure rate was observed in trabeculectomy.